Caffey-Silverman syndrome – a case report of a two-monthold boy with a positive family history - Jakubowska-Pietkiewicz, Elżbieta; Górczewska, Bogumiła; Porczyński, Maciej; Skoczylas, Beata (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Caffey-Silverman disease is a rare, self-limiting disease of infancy. The onset of the disease is usually sudden, and it is characterised by the following symptoms: irritability and/or fever, painful swelling of soft tissues, and excessive bone formation – typical changes in X-ray. The disease usually occurs in the first six months of the child’s life. In most cases, well-researched clinical history, basic laboratory tests, and X-ray imaging are enough to diagnose the disease. We present a case of a two-month-old boy with clinical, radiological symptoms and a positive family history of Caffey-Silverman disease. The baby was admitted to the clinic due to left leg oedema and limitation of mobility in the left hip. In the X-ray, intensive periosteal layering along the mandible and long limb bones was seen. Genetic testing revealed a mutation in the COL1A1 gene. Although Caffey-Silverman disease is a rare collagenopathy, one should not forget its existence.